Traces of a Floating World: Responding to Site in a Print-Based Installation Practice - Schlumbom, Sybille (Auckland University of Technology, 2024)
I am interested in print and installation methods that have the potential to share an impression of environment, matter, and place. To capture these impressions, I explore materials for their ability to collaborate: How do papers differ in their ability to transfer the rust from a mild steel plate without pressure? Can the technique of scroll mounting offer an unfurling of inherently flat works, and in deconstructing the structure of the scroll, extend possibilities for the installation of the works? In my research, I examine encounters with sites through traces of human experience, exploring how I can respond to a site via my print-based installation practice. I am interested in how I can respond and connect to places based on material encounter. My project has developed from my engagement with mokuhanga (Japanese water-based woodblock printing). I aim to determine how concepts and practice of mokuhanga can lead me to develop a site-responsive printing practice, and how I can archive my findings. Concepts in mokuhanga (Japanese water-based print), such as the direct translation of the matrix (e.g. the grain of the wooden plate) and printing techniques that express flow and transition, inform this project's printing methods and conceptual framework. In developing this project, I have explored the rust monotype as both image and trace: as material and site. This has led me to the development of the ‘migratory archive’, a progression of works that record their experience of the site. A ‘site’ is a location that has been recorded in print and contributes to the migratory archive. In adopting the language of the scroll to explore the possibilities of its shape, I found that the form’s open-endedness and flow correspond with the concept of a migratory archive. The making on-site and exhibition space have an archive function, and the works remain under development while moving through the different stages of making and experiencing.